SHRM practices employee and organizational resilient behavior: Implications for open innovation - Khaliq Ur Rehman; Mário Nuno Mata; José Moleiro Martins; Sabita Mariam; Jo\~ao Xavier Rita; Anabela Batista Correia (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The primary objective of this research is to investigate the role of strategic human resource management practices in developing resilient organizational behavior. This research aims to test the mediating function of individual resilient behavior between strategic human resources management practices and resilient organizational behavior. Data was collected from 780 managerial level employees working in small and medium Chinese enterprises in Hubei Province through a self-administrated questionnaire. The Smart partial least square structural equation modeling technique was used for data analysis. The analysis showed a significant positive relationship among SHRM practices, employee resilient behavior, and resilient organizational behavior. Results also show that employee resilient behavior partially mediates the relationship between SHRM practices and resilient organizational behavior. Individual resilient behavior is needed when an organization is in crisis, restructuring, transformation, turbulent, and unfavorable conditions. Without individual resilient behavior, it is difficult for an organization to be resilient. Therefore, strategic human resource management practices are essential to develop an employee's resilience. This research contributed to the body of knowledge by bringing new concepts together. The main contribution was testing the role of individual resilient behavior between strategic human resource management practices and resilient organizational behavior.
Keywords: 650; organizational resilient behavior; individual/employee resilient behavior; strategichuman resource management practices; open innovation; SMEs of China